Pengaruh Promosi Penjualan terhadap Minat Beli Konsumen pada Produk Kosmetik Brand Lokal Somethinc - Delis Kartikawati; Selviana Junaedi Putri; Abdul Yusuf (Economic Reviews Journal, 2024)
This research was conducted on the Somethinc Cosmetic Product Brand with a research place on the Shopee Marketplace and Tiktok Shop, aiming to find out how sales promotion affects consumer buying interest in Somethinc cosmetic products, find out how the impact of sales promotion on consumer buying interest in Somethinc products and what factors influence consumer buying interest in Somethinc products. The research method used is a quantitative method where the type of research is Descriptive. The sample in this study were 100 respondents who had purchased Somethinc cosmetic products on the Shopee Marketplace and Tiktok Shop.